Reshoring concepts: Definitions~and a structured bibliometric review - Muhammad Farooq Siddiqui; Warda Khalid; Muhammad Arsalan (Modern Supply Chain Research and Applications, 2024)
Purpose - The aim of this paper is to clearly mark the clusters in the related literature using bibliometric analysis and draw useful implications for the academic research purposes especially in the stream of Supply Chain Management (SCM). Design/methodology/approach - By employing rigorous selection criteria, sample articles were selected for synthesizing and conducting a bibliometric analysis. This paper tries to identify the significance of the concept of reshoring with the aspect of SCM, operations, logistics etc. Starting from sample selection, systematic selection criteria has been used to generate the database, using Scopus. The sample size was 184. Using VOSViewer, statistical and graphical representations were generated for clusters in the literature that will be useful for judging the trends of research under shoring concepts. Findings - Findings show that unclear difference compared to other supply chain concepts obstructs further theory development within reshoring concepts. To address this challenge, the review categorizes themes and defines boundaries. Based on the analysis findings, this paper advocates for additional research in areas that are crucial but have received limited or no attention. Specifically, there is a need for action research on motivations, governance modes, and location selection concerning reshoring decisions. Research limitations/implications - This review has a few limitations. The absence of publications in other language, than English, may result in a significant loss of knowledge. This research paper cited a few relevant publications in the form of conference papers, industry reports, books, and book chapters. Nonetheless, they were excluded from the organized bibliometric audit. To further advance the knowledge in this field, exploratory longitudinal case studies will bring to focus the changes on manufacturing strategies using the shoring and reshoring stages. Practical implications - A current example of this is a French company named Stil (Terzian, 2020) which brought its glass thermometer production back to its home after the unexpected closure of its suppliers from China. Another Italian firm has restarted production of disposal bio-degradable face masks after 15 years to compete with low-cost alternatives from China (Greco, 2020). Reshoring concepts are now under consideration of organizations including Boeing, Bosch, Phillips and more. Originality/value - To the best of our knowledge, this represents one of the earliest efforts to conceptualize and define reshoring concepts, aiming to distinguish them from one another appropriately. To accomplish this, the earlier demarcated clusters precede this section's classification of reshoring concepts illustrated in Table 8. Based on the synthesis of definitions and thematic clusters above, we have concluded the literature review in this emerging field. It is intended to contribute to theory development and practitioner support in reshoring decisions by clarifying the dimensions.
Keywords: 650; Close shoring; Offshoring; Reshoring